RANCANG BANGUN ALAT PENGASAPAN IKAN DENGAN SIRKULASI ASAP TERSEBAR MERATA - Aris Fiatno; Yanti Yantri Kusuma (ROTOR, 2020)
The processing of smoked fish that is carried out by the XIII Koto Kampar community is still relatively simple, the weaknesses caused by traditional fish smoked include the appearance of being less attractive (partially charred) difficult temperature control and polluting the air. In this research, a fish smoking system was designed using and oven model with a separate combustion chamber, the smoke is flowed through a pipe equipped with a filter and piping design to circulate the smoke evenly to the smoke cabinet. Retrieval of test data in the form of; Efficiency of smoking time by measuring temperature on each shelf and air humidity (RH) in the fumigation chamber, taking proximate content test data to determine moisture, ash, protein and fat content. Temperature testing for 480 minutes while maintaining the temperature between 30-40 ◦C. Humidity at 55% during the curing process and moisture content from 65-48%.